Anomalies and anatomical variations in the coronary arteries and their possible implications (Research, Society and Development, 2024)
With the increase in coronary procedures, understanding the anatomical patterns of the coronary arteries is becoming increasingly crucial, since they can result in implications for the patient. The aim of this study was to carry out a detailed analysis of the coronary arteries of hearts from the Human Anatomy and Pathology Laboratory at the University of Uberaba (UNIUBE). This topic was selected due to its relevance in understanding pathological changes resulting from alterations in blood flow. A cross-sectional analytical observational study was carried out over a period of 20 months: August 2022 to April 2024. The material for the study consisted of 40 preserved cadaveric hearts and data collection was based on a script with previously prepared questions, according to the cardiac anatomy described in the literature. In the study carried out, of the total number of hearts analyzed, four had an irregular coronary pathway, representing a total of 10%. Based on the universally accepted coronary branching pattern, 13 alterations were found, representing a total of 33%. Among them, the main and rarest was the double origin of the anterior descending artery, with one branch originating from the right coronary artery and one from the left coronary artery. Regarding the pattern of coronary dominance, right dominance was predominant in 87% of cases. In general, the research will contribute to a better understanding of the importance of cardiac anatomy for the understanding of clinical events, for the correct performance and interpretation of examinations and for the surgical approach to patients.